Housing Affordability Problems among Young Households - Al Sadat Zyed, Zafirah; Wan Abd Aziz, Wan Nor Azriyati; Hanif, Noor Rosly (Journal of Surveying, Construction and Property, 2016)
Young households are facing various challenges especially as a new entrant in the employment sector. More specifically, there have been worries that young households may not be able to afford a house due to the increasing house prices and cost of living. The aim of this paper is to ascertain the housing affordability problems among young households in Greater Kuala Lumpur. The aim is supported with two objectives which are to identify the housing affordability problems among young households and to discuss the relationship between the identified problems. This paper adopts the case study method and Greater Kuala Lumpur is chosen as the location of the case study. This paper concludes that the main problem faced by young households is limited supply of affordable housing in the market. Even more, the perceived affordable housing in the market is open to all income groups which suggest that young households has to compete with other income groups in the market for homeownership.